2020
DOI: 10.1002/acp.3704
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the formation and duration of flashbulb memories: Evidence from medical diagnosis memories

Abstract: Summary Flashbulb memories are vivid and salient memories for the moment one hears about a surprising, emotional, and significant event. The current research examined flashbulb memories for a loved one's medical diagnosis, focusing on individual and situational factors associated with memory development and endurance over time. An online survey collected memory narratives and subjective ratings from 309 mothers who received a diagnosis of Down syndrome for their child. Time since diagnosis ranged from 1 month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Additionally, a recent study found that the prenatal diagnosis of trisomy 21 constitutes a "flashbulb memory" (FBM); many parents report being able to recall details of the experience several years later (May et al, 2020). The persistence of the FBM was influenced by interactions with medical providers; diminishing of the FBM was associated with the receipt of positive medical support at the diagnosis.…”
Section: Parental Responsementioning
confidence: 99%
“…Additionally, a recent study found that the prenatal diagnosis of trisomy 21 constitutes a "flashbulb memory" (FBM); many parents report being able to recall details of the experience several years later (May et al, 2020). The persistence of the FBM was influenced by interactions with medical providers; diminishing of the FBM was associated with the receipt of positive medical support at the diagnosis.…”
Section: Parental Responsementioning
confidence: 99%
“…Flashbulb memories are described as vivid memories formed when an individual has an emotional or significant experience (Brown & Kulik, 1977; Hirst & Phelps, 2016). A survey of over 300 mothers who had received a diagnosis of Down syndrome for their child, demonstrated that flashbulb memories can last over 20 years following a significant event (May et al, 2020). In this study, an important factor impacting how these memories formed and persisted over time was the support that the patient received from their healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Flashbulb memories are memories for the moment in which one first learned of a surprising and consequential event (Brown & Kulik, 1977). Flashbulb memories are so‐named because of their apparent photograph‐like quality and have been investigated for landmark public events like the death of Princess Diana (Hornstein et al, 2003) or the 9/11 terrorist attacks (Hirst et al, 2009), as well as important personal events like the death of a family member (Rubin & Kozin, 1984) or a serious medical diagnosis (May et al, 2020). While the mechanisms behind flashbulb memories are still debated (see Hirst & Phelps, 2016 for a review), research has demonstrated that they are recalled with greater confidence than everyday memories, but not necessarily with any greater accuracy (Talarico & Rubin, 2003).…”
Section: Methodsmentioning
confidence: 99%